The perception of computer accounting skills of Pamantasan ng Lungsod ng Maynila B.S. Accountancy graduates in relation to their employability in companies in Intramuros - Asturias, Vennesse Rosselle B. et.al. 4 0 16; 5
u
Thesis: (Bachelor of Science in Accountancy) - Pamantasan ng Lungsod ng Maynila, 2017.
Keywords: 2 -- 0; 6; 20; 20; 2